Pengembangan Media Berbasis “Maps of Gita” Pada Materi Pecahan Untuk Siswa Kelas V SD - Hana Lestari; Ima Rahmawati; Sagita Fitriyani; Ridwan Siskandar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to develop “Maps of Gita” learning media on grade V fraction material to help students improve their concept understanding. This research was conducted at SDN Cemplang 01 Bogor Regency and involved 58 grade V students in the 2023/2024 academic year. The research method used is a research and development model using the ADDIE model with stages: (1) Analyze, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. Data were collected in various stages, namely: (1) analysis stage, need assessment and curriculum analysis; (2) design stage includes the preparation of media design, materials, and assessment instruments; (3) development stage includes making media, validation by material experts and media experts, and revision based on input through expert validation questionnaires; (4) implementation stage, involves limited trials to grade V students through pretests and postests to measure students' understanding of concepts before and after using the media; (5) evaluation stage, assessing the effectiveness of the media in improving students' understanding of fraction concepts through student response questionnaires. The results showed that the maps of gita media is feasible to use as a fraction learning media for grade V students. This media obtained a